O jornalismo nas rádios on-line : um estudo da produção de três emissoras - Saccol, Tércio (2016)
The present thesis aims at describing the journalistic production in Brazilian online radio stations through content analysis of Estação Web, Webradio Cultura and Showtime. In order to do so, we analyzed one broadcast from each radio station, and performed interviews with their radio coordinators with the purpose of understanding the context which guides such type of production, its formats, genres, sources, and the languages employed in their broadcasts and the production's rotine. Our theoretical framework is composed by Meditsch (2001, 2010), Ferraretto (2007, 2010, 2014), and Kischinhevsky (2008, 2009 e 2012) for contextualizing and analyzing Radio Journalism; Herreros (2007, 2008), Jenkins (2009), and McChesney (2012) for understanding convergence; Lopez (2009), Prata (2009), and Kichinhevsky (2012) for online radio broadcasting; Traquina (2008), and Wolf (2012) for Journalism; and Lucht (2009) for radiophonic genres and formats. Our conclusion is that the broadcasting formats and Iogics from current radio stations with some informative proposal are similar to those from hertzian radio stations, once they make no experimental use of internet potencialities and give no attention to their audience's particularities on such platform. Even though there is Journalism there, their themes, contents, sources, and languages present no signs of rupturing journalistic and programing paradigms, or breaking with the idea of territoriality.